Catastrophic and Impoverishing Effects of Health Expenditure : New Evidence from the Western Balkans - Bredenkamp, C.; Mendola, M.; Gragnolati, M. (2012)
This paper investigates the effect of health-related expenditure on household welfare in Albania, Bosnia and Herzegovina, Montenegro, Serbia and Kosovo, all of which have undertaken major health sector reform. Two methodologies are used: (i) the incidence and intensity of 'catastrophic' health care expenditure, and (ii) the effect of out-of-pocket payments on poverty headcount and poverty gap measures. Data are drawn from the most recent Living Standards and Measurement Surveys, 2000-05. While our analyses are not without their limitations, and the lack of comparability across instruments precludes a direct comparison across countries, there is no doubt that health expenditure contributes substantially to the impoverishment of households-increasing the incidence of poverty and pushing poor households into deeper poverty-in each country. Both the catastrophic and the impoverishing effects of health expenditures are particularly severe in Albania and Kosovo. Transportation expenditure accounts for a large share of total health expenditures, especially in Albania and Serbia. Informal payments are substantial in all countries, and are particularly high in Albania. As countries in the sub-region continue the process of health system reform, an important policy question should be how to protect vulnerable groups from the catastrophic and impoverishing effects of health care expenditure.